Firm Growth in Family Businesses—The Role of Entrepreneurial Orientation and the Entrepreneurial Activity - Stenholm Pekka; Pukkinen Tommi; Heinonen Jarna (Wiley-Blackwell Publishing, Inc., 2022)
Previous studies show that growth is an important goal for businesses, but little is known of how the entrepreneurial orientation–performance relationship works in family businesses and how this differs from their nonfamily peers. We examine that and how entrepreneurial activity mediates the relationship in family and nonfamily businesses. Our results on 532 firms show that family businesses benefit from innovative orientation, which is both directly and indirectly associated with firm growth via entrepreneurial activity. This association does not exist in nonfamily businesses. Furthermore, risk taking does not influence family business growth even if it does in nonfamily businesses.